Guided implant surgery after free-flap reconstruction: Four-year results from a prospective clinical trial. Issue 8 (October 2015) - Meloni, Silvio Mario; Tallarico, Marco; De Riu, Giacomo; Pisano, Milena; Deledda, Alessandro; Lolli, Francesco Maria; Massarelli, Olindo; Tullio, Antonio
Abstract: Aim: The aim of this prospective clinical study is to assess the 4-year outcomes of implant-supported restorations performed using a computer-guided template-assisted flapless implant surgery approach in patients reconstructed with fibula or iliac crest free flaps. Materials and methods: Twelve jaws in 10 patients were reconstructed with osteomyocutaneous free flap after tumour resection or gunshot wound, after complete healing computer-assisted template-based flapless implant placement, based on prosthetic and aesthetic analysis, was performed using a customized protocol. Treatment success was evaluated using the following parameters: survival of implants/prostheses, prosthetic and biologic complications, marginal bone remodelling, soft tissue parameters and patient satisfaction. Results: A total of 56 implants were placed; the implants ranged between 8 and 16 mm in length and were either 3.5, 4.3 or 5 mm wide. All the patients have reached the 4-year follow-up. Three implants were lost accounting for an overall implant survival rate of 94.6%. No prosthesis were lost. Some complications were recorded. Four years after loading the mean marginal bone loss was 1.43 ± 0.49 mm at the palatal/lingual site and 1.48 ± 0.46 mm at the vestibular site. All the patients showed healthy soft tissues with stable probing depth (4 .93 ± 0.75%) and successful bleeding on probing values (12 ± 5.8%); 90% of patients were satisfied of the treatment at the 4-year follow-up. Conclusions: Computer-guided template-assisted flapless implant surgery seems to be a viable option for patients undergoing reconstruction with free flaps after tumour resection or gunshot trauma, although many challenges remain. A high degree of patient satisfactorily was reported.